1987
DOI: 10.1007/bf00325287
|View full text |Cite
|
Sign up to set email alerts
|

Open finger tip healing and replacement after distal amputation in Rhesus monkey with comparison to limb regeneration in lower vertebrates

Abstract: The left thumbs and great toes of three 8 1/2 month old Rhesus monkeys (Macaca mulatta) were amputated in guillotine fashion one millimeter distal to the base of the nail and allowed to heal by the conservative open wound method. Healing occurred in seven to ten days in these small digits. Each of the thumbs and toes grew back with some blunting and shortening of the digit tips, but were functional. The new structures were cosmetically pleasing as in the human instances. The nails grew essentially to normal si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Digit tip regeneration in various mammalian species, including mice (Muneoka et al, 2008), rats (Said et al, 2004), monkeys (Singer et al, 1987) and humans (Illingworth, 1972) have been described in previous studies. The mouse digit has become a useful model to study mammalian regeneration because of a number of factors, including the description of strain-specific variation in response (Chadwick et al, 2007) and the identification of a regeneration defective mutant line (Han et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Digit tip regeneration in various mammalian species, including mice (Muneoka et al, 2008), rats (Said et al, 2004), monkeys (Singer et al, 1987) and humans (Illingworth, 1972) have been described in previous studies. The mouse digit has become a useful model to study mammalian regeneration because of a number of factors, including the description of strain-specific variation in response (Chadwick et al, 2007) and the identification of a regeneration defective mutant line (Han et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…Digit tip regeneration has also been documented in rats and monkeys (Said et al, 2004; Singer et al, 1987), and there is an extensive clinical literature demonstrating regeneration of human fingertips following amputation injury (Illingworth, 1974; see Muller et al, 1999). In mice, digit tip regeneration has been demonstrated in embryonic, neonatal and adult models (Borgens, 1982; Reginelli et al, 1995; Neufeld and Zhao, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the fact that some mammals exhibit epimorphic regeneration (e.g. rodent and primate digit tips, rabbit and spiny mice ear punches and skin) (Borgens, 1982; Gawriluk et al, 2016; Goss and Grimes, 1975; Han et al, 2008; Joseph and Dyson, 1966; Neufeld and Zhao, 1993; Seifert et al, 2012a; Singer et al, 1987) suggests that regeneration can occur despite a complex adaptive immune system. Different immune system components and inherent physiological differences between mammals and traditional regeneration models like salamanders, newts and zebrafish (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies over the past three decades have shown that mammals, including humans, can regenerate their digit tips provided the amputation plane is distal to the terminal phalangeal joint (Douglas 1972; Illingworth 1974; Borgens 1982; Singer et al 1987). However, Msx1 -deficient mice exhibit impaired fetal digit-tip regeneration, a phenotype that can be rescued in ex vivo cultures in a dose-dependent manner by application of exogenous BMP4 (Han et al 2003).…”
Section: The Molecular Biology Of Regenerationmentioning
confidence: 99%